Digital battery diaphragm and method of manufacturing the same
Patent Information
- Application Number
- KR1020237003046
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-29
- Filing Date
- 2021-03-11
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2041-03-11
Smart Images

Figure 112023009470111-PCT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to the field of diaphragm production technology, and specifically, to a type of digital battery diaphragm and a method for manufacturing the same. Background Technology
[0002] Lithium-ion batteries consist of four core materials: positive electrodes, negative electrodes, separators, and electrolytes. In the structure of a lithium battery, the separator is one of the key inner layer components. Its primary function is to isolate the positive and negative electrodes to prevent contact and short circuits, while simultaneously allowing lithium ions to pass through. Its performance directly determines the advantages and disadvantages of battery life, safety, discharge rate, internal resistance, porosity, liquid absorption rate, and capacity, playing a crucial role in enhancing the overall performance of the battery. The thickness of the battery separator is one of the major factors affecting battery performance and is a key area that we need to research.
[0003] As digital products are upgraded and replaced, the demand in the diaphragm market for ultra-thin diaphragms is intensifying, and at the same time, there is a requirement for ultra-thin diaphragms to further improve performance in aspects such as heat resistance and shrinkage rate. The problem to be solved
[0004] The objective of the present invention is to provide an ultra-thin digital battery diaphragm having good heat resistance and high ion conductivity. means of solving the problem
[0005] To achieve the above objective, the technical solution adopted by the present invention is:
[0006] A type of digital battery diaphragm comprises a substrate film and a polymer coating layer coated on at least one surface of the substrate film, wherein the thickness of the diaphragm is 3 to 10 μm and the ion conductivity is 0.70 to 4.70 mS·cm -1 It is characterized by being.
[0007] Compared to the prior art, the positive effects of the present invention are:
[0008] The digital battery diaphragm of the present invention has a thinner thickness and a smaller footprint compared to commercially available diaphragms, and possesses better heat resistance, thereby maintaining a lower thermal shrinkage rate at high temperatures and providing good safety, effectively preventing dangerous accidents such as internal short circuits in the battery caused by punctures in the diaphragm due to high-temperature shrinkage.
[0009] To achieve the above objective, the technical solution adopted by the present invention is:
[0010] S1: The above organic and inorganic polymers, dispersant, and binder are taken and stirred to mix to obtain a finished slurry, and prepared;
[0011] S2: The finished slurry is coated onto the surface of a substrate film at temperature T1 to obtain a diaphragm product, with a coating stretching speed difference of 0.1% to 10%; then, rewinding is performed, with a rewinding temperature of T2, and the reel-in and reel-out tensions during coating are 1 to 20 N; finally, slitting is performed, with a slitting reeling tension of 0.5 to 30 N and a contact pressure of 0.01 to 0.2 N; and after slitting is completed, a digital battery diaphragm is obtained.
[0012] Compared to the prior art, the positive effects of the present invention are:
[0013] The digital battery diaphragm obtained by employing the manufacturing method of the present invention is thinner than conventional commercially available diaphragms, and in addition to improving the diaphragm porosity and air permeability, it contributes to lowering the battery impedance and the diaphragm's own resistance, effectively improves the ion conductivity of the battery, and further enhances the battery's capacity and speed performance, as well as its battery life. Brief explanation of the drawing
[0014] Figure 1 is a structural diagram of the digital battery diaphragm of the present invention. The symbols in the drawings are: 1 is the substrate film 2 is a polymer coating layer. Specific details for implementing the invention
[0015] The following provides a specific embodiment of the digital battery diaphragm of the present invention.
[0016] Example 1
[0017] As illustrated in FIG. 1, the digital battery diaphragm provided by the present invention comprises a substrate film (1) and a polymer coating layer (2) coated on one surface of the substrate film (1).
[0018] Manufacturing of the above digital battery diaphragm:
[0019] S1: Take a mass fraction of 99% for organic and inorganic polymers, 0.5% for dispersant, and 0.5% for binder; stir at a speed of 800 rm for 1 hour to obtain a finished slurry with a particle size of 2 nm and set aside;
[0020] S2: The finished slurry is coated onto the surface of a substrate film at T1 (50˚C) to obtain a diaphragm product, the coating stretching speed difference is 5%, and it is dried at 50˚C; immediately thereafter, rewinding is performed at a rewinding temperature of T2 (75˚C) and a reeling tension of 10 N; finally, slitting is performed, the slitting reeling tension is 0.5 N and the contact pressure is 0.01 N, and after the slitting is completed, the finished digital battery diaphragm of the present invention is obtained.
[0021] Through testing, the thickness of the finished digital battery diaphragm of the present invention is 7 μm; the air permeability is 200s / 100cc, the porosity is less than or equal to 30%, the thermal shrinkage rate at 200°C is greater than or equal to 8%, the diaphragm intrinsic resistance is greater than or equal to 30 Ω, the resistance is greater than or equal to 100 Ω, and the ionic conductivity is 0.70 to 1.70 mS·cm.-1 am.
[0022] Example 2
[0023] A digital battery diaphragm as shown in FIG. 1 was manufactured according to the manufacturing method of Example 1, and the difference is:
[0024] The slurry completed in step S1 was coated onto the surface of a PE substrate film to obtain a diaphragm product;
[0025] The slitting reel-in tension in step S2 is 10 N.
[0026] Through testing, the thickness of the finished digital battery diaphragm of the present invention is 7 μm; the air permeability is 200 s / 100 cc, the porosity is 30 to 60%, the thermal shrinkage rate at 200 °C is less than or equal to 3%, the diaphragm intrinsic resistance is 0.1 to 30 Ω, the battery resistance is 10 to 100 Ω, and the ionic conductivity is 2.10 to 4.70 mS·cm. -1 am.
[0027] Example 3
[0028] The manufacturing is performed according to the manufacturing method of Example 1, with the difference being: in step S2, the tensile strength of the slitting reel is 30 N, whereas in Example 1 it is 0.5 N.
[0029] Through testing, the thickness of the finished digital battery diaphragm of the present invention is 7 μm; the air permeability is 200 s / 100 cc, the obtained coating film porosity is less than or equal to 30%, the thermal shrinkage rate at 200 °C is greater than or equal to 8%, the diaphragm intrinsic resistance is greater than or equal to 30 Ω, the battery resistance is greater than or equal to 100 Ω, and the ionic conductivity is 0.70 to 1.70 mS·cm. -1 am.
[0030] Example 4
[0031] The manufacturing is performed according to the manufacturing method of Example 1, and the difference is:
[0032] In step S2, the coating elongation speed difference is 10%, and the contact pressure is 0.1 N.
[0033] Through testing, the diaphragm thickness is 3 μm; the air permeability is 300 s / 100 cc, the porosity is less than or equal to 30%, at 200 °C, the thermal shrinkage rate is greater than or equal to 8%, the diaphragm intrinsic resistance is greater than or equal to 30 Ω, the battery resistance is greater than or equal to 100 Ω, and the ionic conductivity is 0.70 to 1.70 mS·cm. -1 am.
[0034] Example 5
[0035] The manufacturing is performed according to the manufacturing method of Example 1, and the difference is:
[0036] In step S1, the injector was stirred at a stirring speed of 700 rpm for 0.01 hours, and a slurry with a particle size of 0.1 nm was obtained.
[0037] In step S2, coating was performed at a coating temperature of T1 (70 °C), the coating elongation speed difference was 0.1%, the reeling tension was 20 N, and it was rewound at T2 (70 °C).
[0038] Through testing, the thickness of the finished digital battery diaphragm of the present invention is 10 μm; the air permeability is 80s / 100cc, the porosity is less than or equal to 30%, the thermal shrinkage rate at 200°C is greater than or equal to 8%, the diaphragm intrinsic resistance is greater than or equal to 30 Ω, the battery resistance is greater than or equal to 100 Ω, and the ionic conductivity is 0.70 to 1.70 mS·cm. -1 am.
[0039] Example 6
[0040] The manufacturing is performed according to the manufacturing method of Example 1, and the difference is:
[0041] In step S1, the organic and inorganic polymers, dispersant, and binder were stirred in a coating machine at a stirring speed of 1300 rpm for 7 hours to obtain a slurry with a particle size of 10 nm;
[0042] In step S2, a finished product slurry with a coating temperature of T1 (60 °C) and a coating elongation rate difference of 6% is coated onto a PE substrate film; the reeling tension during coating is 1 N, and immediately thereafter, rewinding is performed at a rewinding temperature of T2 (100 °C); slitting is performed again, the slitting reeling tension is 5 N, and the contact pressure is 0.2 N.
[0043] Through testing, the thickness of the finished digital battery diaphragm of the present invention is 6 μm; the air permeability is 20 s / 100 cc, the porosity is 30 to 60%, the thermal shrinkage rate at 200 °C is less than or equal to 3%, the diaphragm intrinsic resistance is 0.1 to 30 Ω, the battery resistance is 10 to 100 Ω, and the ionic conductivity is 2.10 to 4.70 mS·cm. -1 am.
[0044] Example 7
[0045] The manufacturing is performed according to the manufacturing method of Example 1, and the difference is:
[0046] In step S2, coating is performed with a coating elongation speed difference of 4%, and the slitting reeling tension is 15 N;
[0047] Through testing, the thickness of the finished digital battery diaphragm of the present invention is 8 μm; the air permeability is 200 s / 100 cc, the coating film porosity is 30 to 60 s / 100 cc, at 200 °C, the thermal shrinkage rate of the diaphragm is less than or equal to 3%, the intrinsic resistance of the diaphragm is within the range of 0.1 to 30 Ω, the battery resistance is 10 to 100 Ω, and the ion conductivity is 2.10 to 4.70 mS·cm. -1 am.
[0048] Table 1 shows the results of the thermal shrinkage rate performance, self-resistance and impedance test, porosity and ion conductivity data of the digital battery diaphragm manufactured under different slitting tension conditions of the present invention.
[0049] Table 2 shows the results of the thermal shrinkage performance test, self-resistance and impedance test, porosity and ion conductivity data of the digital battery diaphragm manufactured under different coating stretching speed difference conditions of the present invention.
[0050] Table 3 shows the results of the thermal shrinkage rate performance test, self-resistance and impedance test, porosity and ion conductivity data of the digital battery diaphragm under different diaphragm thickness conditions of the present invention.
[0051] Table 4 shows the results of the thermal shrinkage performance test, self and impedance test, porosity and ion conductivity data of the digital battery diaphragm of the present invention under different permeability conditions.
[0052] item Digital battery diaphragm with 0.5N slitting tension 10N Slitting Tension Digital Battery Diaphragm Digital battery diaphragm with 30N slitting tension MD Heat Shrink (200 ˚C & 1h) ≥ 8% ≤ 3% ≥ 8% TD Heat Shrinkage (200 ˚C & 1h) ≥ 8% ≤ 3% ≥ 8% Self-resistance (Ω) Battery resistance (Ω) Porosity (s / 100cc) Ionic conductivity / mS·cm -1 ≥ 30≥ 100 ≤ 300.70 to 1.70 0.1 to 3010 to 10030 to 602.10 to 4.70 ≥ 30≥ 100 ≤ 30 0.70 to 1.70
[0053] item Digital battery separator with a coating elongation speed difference of 0.1% Digital battery diaphragm with a coating elongation speed difference of 5% Digital battery separator with a coating stretching speed difference of 10% MD Heat Shrink (200 ˚C & 1h) ≥ 8% ≤ 3% ≥ 8% TD Heat Shrinkage (200 ˚C & 1h) ≥ 8% ≤ 3% ≥ 8% Self-resistance (Ω) Battery resistance (Ω) Porosity (s / 100cc) Ionic conductivity / mS·cm -1 ≥ 30≥ 100≤ 300.70 to 1.70 0.1 to 30 10 to 100 30 to 60 2.10 to 4.70 ≥ 30≥ 100≤ 30 0.70 to 1.70
[0054] item 3 μm thick digital battery diaphragm 7 μm thick digital battery diaphragm 10 μm thick digital battery diaphragm MD Heat Shrink (200 ˚C & 1h) ≥ 8% ≤ 3% ≥ 8% TD Heat Shrinkage (200 ˚C & 1h) ≥ 8% ≤ 3% ≥ 8% Self-resistance (Ω) Battery resistance (Ω) Porosity (s / 100cc) Ionic conductivity / mS·cm -1 ≥ 30≥ 100≤ 300.70 to 1.70 0.1 to 30 10 to 100 30 to 60 2.10 to 4.70 ≥ 30 ≥ 100≤ 30 0.70 to 1.70
[0055] item Speculative rate 80 s / 100cc digital battery diaphragm Speculative rate 200 s / 100cc digital battery diaphragm Speculative rate 300s / 100cc digital battery diaphragm MD Heat Shrink (200 ˚C & 1h) ≥ 8% ≤ 3% ≥ 8% TD Heat Shrinkage (200 ˚C & 1h) ≥ 8% ≤ 3% ≥ 8% Self-resistance (Ω) Battery resistance (Ω) Porosity (s / 100cc) Ionic conductivity / mS·cm -1 ≥ 30≥ 100≤ 300.70 to 1.70 0.1 to 30 10 to 100 30 to 60 2.10 to 4.70 ≥ 30 ≥ 100≤ 30 0.70 to 1.70
[0056] As shown in Table 1, from the battery impedance and self-resistance test results, porosity, and ion conductivity data of the digital battery diaphragm of the present invention, it can be seen that the digital battery diaphragm exhibits different performance at different slitting tensions. When the slitting tensions are 0.5 N and 30 N, the thermal shrinkage rate of the digital battery diaphragm is greater than or equal to 8%, the battery resistance is greater than or equal to 100 Ω, the diaphragm self-resistance is greater than or equal to 30 Ω, the porosity is less than or equal to 30%, and the ion conductivity is 0.70 to 1.70 mS·cm. -1 And; when the slitting tension is 10 N, the thermal shrinkage rate of the digital battery diaphragm is less than or equal to 3%, the battery resistance is 10 to 100 Ω, the self-resistance is 0.1 to 30 Ω, the porosity is 30 to 60%, and the ionic conductivity is 0.70 to 1.70 mS·cm -1As can be seen from the above description, the performance of the digital battery diaphragm is good when the slitting tension is 0.5 to 30 N; and the resistance safety, insulation and heat resistance performance of the digital battery diaphragm under the condition of a slitting tension of 10 N is better, and it has lower impedance and higher ion conductivity, so that the phenomenon of thermal shrinkage or film damage occurring at high temperatures can be effectively avoided, which causes the positive and negative electrodes to come into direct contact and cause an internal short circuit in the battery and cause safety problems, thus having great potential for development.
[0057] As shown in Table 2, from the battery impedance and self-resistance test results, porosity, and ion conductivity data of the digital battery diaphragm of the present invention, it can be seen that the digital battery diaphragm exhibits different performance at different slitting tensions. When the coating elongation rate difference is 0.1% and 10%, the thermal shrinkage rate of the digital battery diaphragm is greater than or equal to 8%, the battery resistance is greater than or equal to 100 Ω, the diaphragm self-resistance is greater than or equal to 30 Ω, the porosity is less than or equal to 30%, and the ion conductivity is 0.70 to 1.70 mS·cm. -1 And; when the coating stretching rate difference is 5%, the thermal shrinkage rate of the digital battery diaphragm is less than or equal to 3%, the battery resistance is 10 to 100 Ω, the diaphragm intrinsic resistance is 0.1 to 30 Ω, the porosity is 30 to 60%, and the ionic conductivity is 2.10 to 4.70 mS·cm -1As can be seen from the above description, the performance of the digital battery diaphragm is good when the coating elongation rate difference is 0.1% to 10%; and the resistance safety, insulation and heat resistance performance of the digital battery diaphragm under the condition where the coating elongation rate difference is 5% is better, and it has lower impedance and higher ion conductivity, so that the diaphragm can effectively avoid the phenomenon of thermal shrinkage or film damage occurring at high temperatures, the positive and negative electrodes coming into direct contact, causing an internal short circuit in the battery, and causing safety problems, thus having great potential for development.
[0058] As shown in Table 3, from the battery impedance and self-resistance test results, porosity, air permeability, and ionic conductivity data of the digital battery diaphragm of the present invention, it can be seen that the digital battery diaphragm exhibits different performance at different slitting tensions. When the diaphragm thickness is 3 μm and 10 μm, the thermal shrinkage rate of the digital battery diaphragm is greater than or equal to 8%, the battery resistance is greater than or equal to 100 Ω, the self-resistance is greater than or equal to 30 Ω, the porosity is less than or equal to 30%, and the ionic conductivity is 0.70 to 1.70 mS·cm. -1 And; when the coating thickness is 7 μm, the thermal shrinkage rate of the digital battery separator is less than or equal to 3%, the battery resistance is 10 to 100 Ω, the separator intrinsic resistance is 0.1 to 30 Ω, the porosity is 30 to 60%, and the ionic conductivity is 2.10 to 4.70 mS·cm -1As can be seen from the above description, the performance of the digital battery diaphragm is good when the diaphragm thickness is 3 to 10 μm; and the resistance safety, insulation and heat resistance performance of the digital battery diaphragm under the condition where the diaphragm thickness is 7 μm is even better, and it has lower impedance and higher ion conductivity, so that the phenomenon of thermal shrinkage or film damage occurring at high temperatures can be effectively avoided, and the positive and negative electrodes can come into direct contact, causing an internal short circuit in the battery and causing safety problems, thus having great potential for development.
[0059] As shown in Table 4, from the battery impedance and self-resistance test results, porosity, and ion conductivity data of the digital battery diaphragm of the present invention, it can be seen that the digital battery diaphragm exhibits different performance at different permeability rates. When the diaphragm permeability is 80 s / 100cc and 300 s / 100cc, the thermal shrinkage rate of the digital battery diaphragm is greater than or equal to 8%, the battery resistance is greater than or equal to 100 Ω, the self-resistance is greater than or equal to 30 Ω, the porosity is less than or equal to 30%, and the ion conductivity is 0.70 to 1.70 mS·cm. -1 And; when the permeability is 200 s / 100cc, the thermal shrinkage rate of the digital battery diaphragm is greater than or equal to 3%, the battery resistance is 10 to 100 Ω, the diaphragm intrinsic resistance is 0.1 to 30 Ω, the porosity is 30 to 60%, and the ionic conductivity is 2.10 to 4.70 mS·cm -1As can be seen from the above, the performance of the digital battery diaphragm is good when the permeability is 80-300 s / 100cc; and here, the resistance safety, insulation and heat resistance performance of the digital battery diaphragm under conditions where the permeability is 200 s / 100cc is better, and it has lower impedance and higher ion conductivity, so that the phenomenon of thermal shrinkage or film damage occurring at high temperatures can be effectively avoided, which causes the positive and negative electrodes to come into direct contact and cause an internal short circuit in the battery and cause safety problems, thus having great potential for development.
[0060] The above description is merely a preferred embodiment of the present invention, and it should be noted that a person skilled in the art may make slight improvements and adaptations without departing from the spirit of the present invention, and such improvements and adaptations are also considered to be within the scope of protection of the present invention.
Claims
Claim 1 A method for manufacturing a digital battery diaphragm comprising a substrate film and a polymer coating layer coated on at least one surface of the substrate film, comprising: S1: taking organic and inorganic polymers, a dispersant, and a binder, stirring and mixing them to obtain a finished slurry, and preparing it; S2: coating the finished slurry onto the surface of the substrate film at temperature T1 to obtain a diaphragm product, wherein the coating stretching speed difference is 0.1% to 10% and the reeling tension during coating is 1 to 20 N; subsequently, rewinding is performed, wherein the rewinding temperature is T2; finally, slitting is performed, wherein the slitting reeling tension is 0.5 to 30 N and the contact pressure is 0.01 to 0.2 N; and wherein, after the completion of slitting, a digital battery diaphragm is obtained, wherein the thickness of the diaphragm is 3 to 10 μm and the ion conductivity is 0.70 to 4.70 mS·cm -1 A manufacturing method characterized in that, in the polymer coating layer, the mass fraction of each raw material is: organic and inorganic polymer: 99%, dispersant: 0.5%, binder: 0.5%. Claim 2 A manufacturing method according to claim 1, wherein the diaphragm has an air permeability of 80 to 300 s / 100cc. Claim 3 In claim 1, the diaphragm has a thickness of 6 to 8 μm and an ion conductivity of 2.10 to 4.70 mS·cm. -1 A manufacturing method characterized in that the above diaphragm has an MD thermal shrinkage rate and a TD thermal shrinkage rate at 200 °C that are less than or equal to 3%. Claim 4 A manufacturing method according to claim 3, characterized in that the diaphragm has a self-resistance of the main body of 0.1 to 30 Ω and a porosity of the diaphragm of 30 to 60%. Claim 5 delete Claim 6 delete Claim 7 A manufacturing method according to claim 1, wherein in step S1, the organic and inorganic polymers, dispersant, and binder are stirred at a speed of 700 to 1300 rpm for 0.01 to 7 hours to obtain a finished slurry having a particle size of 0.1 to 10 nm; and wherein in step 2, T1 is 50 to 70 °C and T2 is 70 to 100 °C.
Citation Information
Patent Citations
Separator for electronic component and manufacturing method thereof
JP2006019146A
A separator for electrochemical device
KR1020150070979A
